Heparan sulphate proteoglycans: the sweet side of development. - Häcker, U.; Nybakken, K.; Perrimon, N. (Nature Reviews. Molecular Cell Biology, 2005)
Pattern formation during development is controlled to a great extent by a small number of conserved signal transduction pathways that are activated by extracellular ligands such as Hedgehog, Wingless or Decapentaplegic. Genetic experiments have identified heparan sulphate proteoglycans (HSPGs) as important regulators of the tissue distribution of these extracellular signalling molecules. Several recent reports provide important new insights into the mechanisms by which HSPGs function during development.